The feasibility and efficacy of implementing a focused cardiac ultrasound course into a medical school curriculum - Kobal, Sergio L. (BMC Med Educ, 2017)
BACKGROUND: Teaching cardiac ultrasound to medical students in a brief course is a challenge. We aimed to evaluate the feasibility of teaching large groups of medical students the acquisition and interpretation of cardiac ultrasound images using a pocket ultrasound device (PUD) in a short, specially designed course. METHODS: Thirty-one medical students in their first clinical year participated in the study. All were novices in the use of cardiac ultrasound. The training consisted of 4 hours of frontal lectures and 4 hours of hands-on training. Students were encouraged to use PUD for individual practice. Finally, the students’ proficiency in the acquisition of ultrasound images and their ability to recognize normal and pathological states were evaluated. RESULTS: Sixteen of 27 (59%) students were able to demonstrate all main ultrasound views (parasternal, apical, and subcostal views) in a six-minute test. The most obtainable view was the parasternal long-axis view (89%) and the least obtainable was the subcostal view (58%). Ninety-seven percent of students correctly differentiated normal from severely reduced left ventricular function, 100% correctly differentiated a normal right ventricle from a severely hypokinetic one, 100% correctly differentiated a normal mitral valve from a rheumatic one, and 88% correctly differentiated a normal aortic valve from a calcified one, while 95% of them correctly identified the presence of pericardial effusion. CONCLUSIONS: Training of medical students in cardiac ultrasound during the first clinical year using a short, focused course is feasible and enables students with modest ability to acquire the main transthoracic ultrasound views and gain proficiency in the diagnosis of a limited number of cardiac pathologies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12909-017-0928-x) contains supplementary material, which is available to authorized users.